ECB Spillovers and Domestic Monetary Policy Effectiveness in Small Open Economies - Saskia ter Ellen; Edvard Jansen; Nina Larsson Midthjell (Norges Bank, 2018)
In this paper we study financial spillovers from the European Central Bank's (ECB) monetary policy and communication, and whether they have consequences for the effectiveness of domestic monetary policy of small open economies. Recent work suggests that the "trilemma" in international economics as we used to know it, is actually a dilemma: small open economies with floating exchange rate regimes can only have independent monetary policies when the capital account is managed. Our findings show that domestic monetary policy is still effective, but that spillover effects, particularly from the ECB's communication, reduce domestic control over the longer end of the yield curve.
hdl:11250/2577123
Keywords: E43; E44; E52; E58; G12; 330; monetary policy; forward guidance; international spillovers; asset prices; small open economies